Elucidating the interaction between Brassica napus and Rhizoctonia solani AG 2-1 - Drizou, Fryni (2018)
Brassica napus, oilseed rape (OSR), is a worldwide cultivated crop belonging to the family Brassicaceae, broadly used in crop rotations with cereals. Production is focused on oil for human consumption, biodiesel and feedstock. OSR has undergone intensive breeding for optimization of oil content, disease resistance and augmentation of yields, and today is considered one of the most profitable crops. Nonetheless, oilseed rape is the primary host for the necrotrophic soil-borne pathogen Rhizoctonia solani anastomosis group (AG) 2-1. Infection of seedlings causes damping off disease and decreases crop establishment and yields. AG 2-1 is the most prevalent AG of R. solani in wheat fields in the UK. Currently there is no OSR germplasm resistant to R. solani AG 2-1. Available control methods include cultural practices and chemical seed treatments, which aim to postpone the infection and hence improve crop establishment. Changes in agronomic practices and crop management, including choice of cultivars, tillage, application of fertilisers and pesticides, mean that there is a danger of future outbreaks of diseases that in the past were not considered as major problem. This includes R. solani AG 2-1 which can infect other rotational crops as well and due to its saprophytic nature remains in the fields for years. The aim of the PhD was to elucidate interactions between R. solani AG 2-1 and B. napus, by identifying potential resistant traits and understanding how the pathogen counteracts OSR plant defences. The first objective was to develop and compare different high-throughput screening methods that could be used for the phenotyping of OSR germplasm interactions with R. solani AG 2-1. Four methods were developed and compared: (1) nutrient media plates, (2) compost trays, (3) light expanded clay aggregate (LECA) trays and (4) a hydroponic pouch and wick system. Inoculation of LECA was the most suitable method for screening disease caused by AG 2-1 to OSR germplasm, because it allowed the detection of differences in disease severity between the tested OSR genotypes 5 days post infection (dpi) and also to conduct measurements in whole plants. The second objective was to identify any sources of disease resistance by screening a diversity of OSR germplasm. To start the screening, I selected randomly germplasm from commercial cultivars and parental lines of mapping populations that was available in our seed bank. Overall, the germplasm tested consisted of commercial cultivars, genotypes from diversity sets and a mapping population. All genotypes tested appeared to be susceptible to AG 2-1 infection as shown by high disease levels, reduced emergence and survival. Additionally, I tested if any induced defence responses from exposure to disease could be inherited in the next generation through an epigenetic stress response. However, all progeny plants were also highly susceptible indicating that there was no evidence for transgenerational induction of resistance in this system. The third objective was to gain insight into OSR plant defences when exposed to a combination of attacking organisms, as this often occurs in real field situations. I investigated the role of M. persicae infestation on OSR susceptibility to R. solani AG 2-1. There was no effect of AG 2-1 infection on aphid performance. However, M. persicae infestation resulted in significantly more disease symptoms in B. napus cv. ‘Canard’ plants although there were no significant differences in the amount of fungal DNA. Marker genes LOX3 and MYC2 had an augmented expression under AG 2-1 treatment but were downregulated in plants exposed to both aphids and pathogen. Hence, it appears that aphid infestation induced changes in the jasmonic acid (JA) signalling pathway, which resulted in the increased susceptibility to AG 2-1. In conclusion, the present work provided a new high-throughput screening method suitable to phenotype disease by AG 2-1 in the early seedling stage within a short time period. Unfortunately, the current results confirm previous studies indicating that AG 2-1 is an extremely aggressive isolate to OSR germplasm that lacks genetic resistance. Nonetheless, the observed differences between the germplasm tested in the present work suggest that there are potential tolerant traits. For the first time, the current work provided evidence that M. persicae infestation can negatively affect plant defences against R. solani AG 2-1, through suppression of genes involved in JA signalling. Additionally, it was demonstrated that R. solani AG 2-1 induces the activation of defence mechanism related to both JA and salicylic acid (SA) pathways. Future studies aiming to identify resistant/tolerant traits should screen wider Brassica germplasm, including wild species. Additionally, it will be particularly interesting to explore how R. solani overcomes OSR defences by examining the expression of a broader array of genes involved in plant defence mechanisms.